Low-dose ionizing radiation attenuates mast cell migration through suppression of monocyte chemoattractant protein-1 (MCP-1) expression by Nr4a2. (2nd November 2019) - Song, Chin-Hee; Joo, Hae Mi; Han, So Hyun; Kim, Jeong-In; Nam, Seon Young; Kim, Ji Young
Abstract: Purpose: The aim of this study was to investigate whether low-dose ionizing radiation attenuates mast cell migration by modulating migration-associated signaling pathways and the expression of chemotactic cytokines. Materials and methods: IgE-sensitized RBL-2H3 mast cells were exposed with ionizing radiation at 0.01, 0.05, 0.1, or 0.5 Gy using a 137 Cs γ-irradiator and stimulated with 2, 4-dinitrophenol-human serum albumin. Cell migration was determined using a transwell assay system, F-actin distribution using Alex Fluor 488-conjugated phalloidin, expression of various signaling proteins by Western blotting, mRNA expression by RT-PCR. Results: Low-dose ionizing radiation significantly suppressed mast cell migration induced by IgE-mediated mast cell activation. Furthermore, low-dose ionizing radiation altered cell morphology, as reflected by changes in F-actin distribution, and inhibited the activation of PI3K, Btk, Rac1, and Cdc42. These effects were mediated by Nr4a2, an immune-modulating factor. Knockdown of Nr4a2 reduced mast cell migration, inhibited the PI3K and Btk signaling pathways, and reduced expression of the chemotactic cytokine monocyte chemoattractant protein-1 (MCP-1). We further demonstrated that direct blockade of MCP-1 using neutralizing antibodies inhibits mast cell migration. Conclusion: Low-dose ionizing radiation inhibits mast cell migration through the regulation production of MCP-1 by Nr4a2 in the activated mast cell system.